2014
DOI: 10.1126/science.1245316
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals Dynamic, Random Monoallelic Gene Expression in Mammalian Cells

Abstract: Expression from both alleles is generally observed in analyses of diploid cell populations, but studies addressing allelic expression patterns genome-wide in single cells are lacking. Here, we present global analyses of allelic expression across individual cells of mouse preimplantation embryos of mixed background (CAST/EiJ × C57BL/6J). We discovered abundant (12 to 24%) monoallelic expression of autosomal genes and that expression of the two alleles occurs independently. The monoallelic expression appeared ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
1,239
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,243 publications
(1,308 citation statements)
references
References 33 publications
64
1,239
4
1
Order By: Relevance
“…Previously, our lab and others demonstrated that single-cell RNA-seq facilitates the identification of ASE patterns. [21][22][23][24] In this study, we sequenced the RNA of 1,084 single fibroblasts from 5 individuals. For 2 of these individuals, the parental DNA was available.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our lab and others demonstrated that single-cell RNA-seq facilitates the identification of ASE patterns. [21][22][23][24] In this study, we sequenced the RNA of 1,084 single fibroblasts from 5 individuals. For 2 of these individuals, the parental DNA was available.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we test netSmooth on 269 isolated cells from mouse embryos at different stages of pre-implantation development between oocyte and blastocyst, as well as 5 liver cells and 10 fibroblast cells 18 . The authors of this study demonstrated that lower dimension embeddings capture much of the developmental trajectory ( Figure 4a, Figure S4a, Figure S5a).…”
Section: Resultsmentioning
confidence: 99%
“…The embryonic 18 and glioblastoma 19 datasets were obtained from conquer 22 , a repository of uniformly processed scRNA-seq datasets. The datasets are available publicly, see Table 1.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular transitions can be studied by defining cell states using hierarchical clustering or principal component analysis‐like methods. The approach has been applied to show how cells change gradually along the developmental pathway from zygote to the late blastocyst 53. In future, a similar approach can be applied to the in vivo immune cell activation/inactivation dynamics and their dysfunction.…”
Section: Future Directionsmentioning
confidence: 99%